Letter (copy) : Spain - Citrine, Walter, 1887-1983
022_0011-001 WMC/WJB/AC/593 International 24th March, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, avenue d'Orsay, PARIS VIIe. Dear Comrade Schevenels, SPAIN. In the discussion today by the General Council relating to the Spanish situation, mention was made of the attack upon our Chairman, Mr. E. Bevin, which appeared in the "Daily Worker", owing to his speech at the recent International Conference held in London. You will know that we have already written to you about an article in "L'Humanité", which criticises the attitude taken up by the British delegation. The General Council are particularly disturbed by the discovery that a representative of the "Daily Worker", a Mr. Frank Pitcairn, was actually present at the Conference, representing our Spanish comrades. For your information we are enclosing a copy of his photograph. Comrade Stolz will probably recognise him. He will remember that his attention was drawn to this man. When he was challenged, he produced an official credential, showing that he had been appointed as a member of the Spanish delegation. Perhaps you will give us the complete list of the names of the delegation. The Council would be glad if you would kindly make enquiries of the Spanish comrades in order to clear up this matter. The incident has made a profound impression upon the General Council, and I am convinced that it will be difficult to get them to accept proposals for future conferences of this character, unless there is an absolute certainty that there will be no more of these deliberate breaches of confidence. Yours faithfully, General Secretary. 292/946/22/10